Ageing Deep-Sea Black Coral Bathypathes patula - Marriott, Peter; Tracey, Dianne Margaret; Bostock, Helen; Hitt, Nicholas; Fallon, Stewart J. (Frontiers in Marine Science, 2020)
Deep-sea corals are a highly diverse group of marine organisms, several of which are characterised by slow growth and extreme longevity. Due to their fragile forms, skeletal composition, and location, they are vulnerable to various anthropogenic threats with some groups expected to have little to no ability to recover. Ten individual colonies of the Antipatharian black coral species Bathypathes patula were selected from the NIWA National Invertebrate Collection (NIC) for the purposes of this ageing study. Corals were selected based on their size, completeness of the colony (whole colony from base to tip), and the regional water mass within which they grew. Corals from the Chatham Rise and the Bay of Plenty were selected as the water masses for these two regions are reasonably well understood, and this work will support other comparable ageing work on deep-sea corals in these regions. Thin section preparations of the main-stem of the ten specimens were observed with compound microscopes. Two interpretation protocols were defined to describe the zone structure observed, both coarse and fine zones, and counts were made of these structures. Four of the specimens were also sampled for radiocarbon assay. The radiocarbon isotope (14C) age data results were used to independently verify if either of the developed zone counting protocols reflected annual periodicity. Neither method was verified, indicating the developed zone counting protocols could not be used to generate reliable age estimates for B. patula. The identification of one of the selected coral colonies was revised during the study to Bathypathes cf. conferta. This specimen was aged using zone counts but 14C dates were lost during processing. Twenty radiocarbon results were used to derive the age and growth rates estimates presented here. The radiocarbon results from this work show B. patula to be a long-lived species, attaining ages in excess of 385 years, with linear growth rates of 5.2–9.6 mm yr-1, and radial growth rates ranging from 11.1–35.7 m yr-1. The delicate nature of these organisms along with their longevity and slow growth rates means a low resilience and low recoverability from anthropogenic activities such as fishing and mining.